Pengaruh Kinerja Lingkungan, Ukuran Perusahaan dan Islamic Governance Score Terhadap Pengungkapan Islamic Social Reporting (ISR) Pada Perusahaan Yang Terdaftar di Indeks Saham Syariah Indonesia - Amanda, Annisa Rizka; Harmain, Hendra; Syarvina, Wahyu (Universitas Labuhanbatu, 2023)
This study aims to obtain empirical evidence of the influence of 3 (three) independent variables, namely environmental performance, company size and Islamic Governance Score on the dependent variable, namely the disclosure of Islamic Social Reporting (ISR). The type of data used in this study is quantitative data obtained from the annual financial reports of companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period as well as other data needed in this research. The data analysis technique uses a panel data regression model. The results show that environmental performance has no effect on disclosure of Islamic Social Reporting (ISR) in companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period, company size has a positive and significant effect on disclosure of Islamic Social Reporting (ISR) in listed companies in the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period and the Islamic Governance Score has a positive and significant effect on the disclosure of Islamic Social Reporting (ISR) in companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period. Simultaneously it shows that environmental performance, company size and Islamic Governance Score have an effect on the disclosure of Islamic Social Reporting in companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2020 period.